Vitamin A and dehydrated alfalfa fed individually and in combination with and without Aureomycin in a steer fattening ration - Richardson, D.; Smith, E.F.; Kingsley, K.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Hereford yearling steers in this test were used in a previous bluestem pasture grazing test. After the grazing test was completed, they were assigned to six lots of 10 animals each on the basis of weight and uniformity to compare the value of dehydrated alfalfa as a source of vitamin A with preformed vitamin A, both individually and in combination with and without Aureomycin. The supplements supplied the same amount of protein, calcium, and phosphorus in each lot. Vitamin A value of carotene was figured on the dehydrated alfalfa at 400 I.U. per milligram of carotene; 10,000 I.U. of Vitamin A per head was fed daily for the first 84 days and 15,000 I.U. units for the remainder of the test; 70 milligrams of Aureomycin was fed per head daily. After the steers were on feed, silage was limited to 20 pounds per head daily; however, grain was fed ad lib.
Keywords: Beef; Alfalfa; Aureomycin; Steer